E-094 Correlation between total thrombus leukocyte count and outcome at discharge post mechanical thrombectomy. (4th August 2020) - Chen, P; Sheriff, F; Inam, M; Lopez-Rivera, V; Lekka, E; Oni-Orisan, A; Finger, C; Hudobenko, J; Morales, D; Seth, S; Manwani, B
Abstract : Background: Ischemic stroke is increasingly being realized to be an inflammatory disease. Post stroke peripheral leukocyte recruitment to the brain has been well studied in preclinical models of ischemic stroke. Limited studies have examined the intravascular inflammatory milieu in the brain during ischemia. Thrombi collected from ischemic stroke thrombectomy patients can be valuable resources for these studies. There are a handful of studies focusing on the role of inflammation in clot pathology. Small studies have demonstrated that higher thrombus leukocyte fraction and neutrophil to lymphocyte ratios are associated with technically challenging procedures and a trend to worse long term outcomes. Methods: We prospectively collected 44 thrombi obtained during mechanical thrombectomy in patients with LVO ischemic strokes. Data on demographics, clinical, procedural and clot composition were collected. These thrombi were paraffin embedded, sliced and stained with Hematoxylin and Eosin. Images were taken using a light microscope, 20 and 40x magnification. Image J was used to quantify the leukocytes using previously described methods. The median and maximum leukocyte count of the 5 analyzed images for each patient was used for analysis. Outcome was defined as location at discharge with discharge to home or rehab considered favorable. Fisher's exact and Mann-Whitney U tests were used for comparison of categorical and continuous variables, respectively. Multivariate logistic regression was then performed. Pearson's correlation coefficient was used to assess the relationship of leukocytes to NIHSS and time from symptom onset to groin puncture. Results: Among 44 patients with large vessel occlusion, median age was 65.5 years [59–73 years], 15 (35%) were women, 84% had hypertension, 43% had atrial fibrillation, and 24% had hyperlipidemia. Median NIHSS was 18 [14–22] and median leukocyte count in the thrombi was 537 [397–794.5]. NIHSS on admission had a negative correlation with favorable discharge outcome as defined by discharge to home or rehab (OR=0.44, p=0.021). Total leukocyte count did not correlate with NIHSS at arrival (r=-0.0086; P=0.9560), number of passes, TICI score nor with time from last seen well to groin puncture (r=0.1937; P=0.2134). On multivariate analysis, there was a negative correlation between maximum thrombus leukocyte count and discharge outcome (OR=0.066, p=0.048) after accounting for age and NIHSS on admission. Conclusion: Leukocyte count in thrombi retrieved post mechanical thrombectomy shows a significant negative correlation with discharge outcome in patients with ischemic stroke. Our study focused on total leukocyte count and corroborates with previous studies which focused on leukocyte fraction. Further studies using flow cytometry and concomitant peripheral blood analysis along with long term outcome measures are necessary to better define this relationship and understand role of inflammation in LVO stroke. Disclosures: P. Chen: None. F. Sheriff: None. M. Inam: None. V. Lopez-Rivera: None. E. Lekka: None. A. Oni-Orisan: None. C. Finger: None. J. Hudobenko: None. D. Morales: None. S. Seth: None. B. Manwani: None.